Challenging the five-stage model for e-learning: a new approach - Pam Moule (Association for Learning Technology, 2007)
The five-stage approach to e-moderating has provided a coherent model upon which to base online learning design in higher education. However, despite its growing popularity, there are concerns that the model is becoming a dominant discourse, being adapted as a template for the design of all online teaching and learning, to the exclusion of other ideas. It is suggested that the five-stage model may not be the panacea it appears and alternative models of e-learning cannot be ignored. This paper reviews the five-stage model and contrasts it with a new conceptual model, ‘the e-learning ladder', conceived as part of research with healthcare students in the higher education setting.